AN EXPLORATION OF STUDENTS’ PERCEPTIONS TOWARD THE USE OF DEEPL TRANSLATOR IN ENGLISH LANGUAGE LEARNING - Muh. Ichsan Mahdi Mastie; Maemuna Muhayyang; Muhammad Arham (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study aims to explore students perceive of the use of DeepLTranslator. This research used a qualitative descriptive method. The data collection in this study was carried out by interviewing 4 students from the English Department at Universitas Negeri Makassar. The results of this study found that students perceive DeepL as an effective and user-friendly tool for learning English, particularly in understanding texts, writing, and checking grammar. The students said that DeepL translations are more natural and accurate than other tools like Google Translate. Its simple interface and practical features make it accessible even for beginners. However, some students noted limitations, such as a limited number of available languages and the need for a premium account to access full features. Despite its usefulness, students do not rely solely on DeepL and often attempt translate independently. Their openness to trying other tools reflects digital literacy and learner autonomy Keywords: Students’ Perception, DeepL Translator, English Language Learning